Seroepidemiological study of Toxoplasma gondii in Peruvian goats and its association with risk factors - Chávez V., Amanda (2021)
The aim of this study was to determine the seroprevalence of Toxoplasma gondii and its association with risk factors in Peruvian goats. A total of 1119 goat sera collected between 2017-2018 from 23 of the 24 departments of the country by the National Animal Health Service (SENASA) to monitor Brucella melitensis were evaluated. The number of samples was proportional to the goat population of each department. The variables age (<1, 1-3, >3 years), sex, origin (North Coast Zone, Central-South Coast Zone, Sierra-East Zone, altitude (0-500, >500-2500, >2500 m) and type of rearing (intensive, extensive) were considered. The sera were analysed with a commercial multi-species indirect ELISA kit and the risk factors were determined by logistic regression. The overall prevalence of T. gondii was 28.15% (95% CI: 25.5-30.9). The highest prevalences were found in the Sierra-East and Central-South Coast), at an altitude <2500 m and under intensive rearing.